Meninjau Tanggungjawab Sosial Perusahaan dalam Pendekatan Kapabilitas - Pinurba Parama Pratiyudha (Sospol : Jurnal Sosial Politik, 2020)
This paper departs from the discourse of the paradigm of social development in third world countries. The first discourse reviews the critics of the broad state in social development. It supports the non-state actors to take a part in development through corporate social responsibility (CSR). The second discourse departs from economic development which weakens the capability of the individual in achieving development itself. The concept of the capability approach in human development emerged as a solution to create inclusive welfare. This paper itself raises these two things in one discussion related to the role of CSR in relation to the development of human capabilities. Taking an analysis of the Program Desa Mandiri Energi by PJB UP Paiton, the study examines the role of CSR activities in supporting community capabilities. This paper argues that the existence of CSR provides a strong contribution to strengthening the capabilities of the community that has developed from the past. However, in the subsequent findings, there are several aspects of CSR programs that still several actions to be developed and improved human capabilities.